Nutritional Risk, Frailty, and Inflammatory Biomarkers as Correlates of Infection Severity and Healing Risk in Patients with Diabetic Foot Ulcers: A Hospital-Based Cross-Sectional Study - Samsul Adipati; Akbar Faruk; Asmat Burhan (Journal of Wound Research and Technology, 2026)
Background: Diabetic foot ulcers (DFU) remain a major clinical problem because severe infection and poor healing increase hospitalization, amputation, and mortality. Patient-level factors such as nutritional vulnerability, frailty, and inflammatory burden may be clinically relevant, but integrated hospital-based evidence remains limited, particularly in Indonesian wound-care settings. Aim: To examine whether nutritional risk, frailty, and inflammatory biomarkers were associated with infection severity and healing risk in hospitalized patients with diabetic foot ulcers. Approach: This hospital-based cross-sectional study included 91 adults with active diabetic foot ulcers at General Hospital Bhakti Rahayu. Consecutive sampling was used. Eligible participants had diabetes, an active ulcer, and complete clinical and laboratory data. Ordinal and binary logistic regression analyses were performed using IBM SPSS Statistics version 19 Results: The mean (SD) age was 58.6 (10.9) years, 62.6% were male, 73.6% had nutritional risk, and 41.8% were frail. Infection severity was mild in 31.9%, moderate in 47.3%, and severe in 20.9%. Higher infection severity was associated with nutritional risk (aOR, 3.18; 95% CI, 1.05-9.67; P = .04), frailty (aOR, 2.24; 95% CI, 1.01-4.98; P = .048), and higher CRP per 10-mg/L increase (aOR, 1.22; 95% CI, 1.05-1.42; P = .01) Conclusions: Nutritional risk, frailty, and inflammatory burden were associated with greater infection severity in hospitalized patients with diabetic foot ulcers. Implication for Nursing Practice: Nursing assessment of diabetic foot ulcers may benefit from integrating nutritional screening, frailty evaluation, and inflammatory biomarker review to support earlier risk identification and more individualized wound-care planning.